1992
DOI: 10.1029/91gl01182
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of teleseismic travel time residuals for velocity structure in the Larderello Geothermal Field, Italy

Abstract: The analysis of teleseismic travel time residuals recorded on the Larderello Seismic Network of central Italy has revealed a sharp low velocity zone (LVZ) in the center of the geothermal production area. Residuals from 101 teleseismic events are inverted to produce an image of a region of anomalously low velocities which we have interpreted to be a series of intrusive magmatic bodies. The top of this anomalous region is constrained to be below 6 km in depth from local earthquake seismicity patterns and extends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…A similar scenario is envisaged for the present-day Larderello geothermal system where cooling granitoids are hypothesized at depth of about 6-8 km (Foley et al 1992). In the Larderello area, two geothermal reservoirs are exploited: the shallower located within the late Triassic evaporites, the deeper within the crystalline basement, correspondending to cataclastic zones (Barelli et al 2000;Boyce et al 2003;Bellani et al 2004 and references therein), representing the present-day analogues of the Boccheggiano fault damage zone.…”
Section: Discussionmentioning
confidence: 94%
“…A similar scenario is envisaged for the present-day Larderello geothermal system where cooling granitoids are hypothesized at depth of about 6-8 km (Foley et al 1992). In the Larderello area, two geothermal reservoirs are exploited: the shallower located within the late Triassic evaporites, the deeper within the crystalline basement, correspondending to cataclastic zones (Barelli et al 2000;Boyce et al 2003;Bellani et al 2004 and references therein), representing the present-day analogues of the Boccheggiano fault damage zone.…”
Section: Discussionmentioning
confidence: 94%
“…Subsequent extension and crustal thinning in the Late Miocene produced anatectic melts and the emplacement of granitic batholiths Franceschini 1995;Boccaletti et al 1997). Geophysical evidence suggests a partially molten batholith is still present below the Larderello geothermal area (Foley et al 1992), and drill holes (to depths of 4.5 km) have encountered temperatures in excess of 400°C (Gianelli and Ruggieri 2002). Stratigraphy is varied and complex, consisting of (from top to bottom) Neogene sediments, allochthonous ophiolite and fl ysch sequences of JurassicEocene age, the Tuscan Nappe of Upper Triassic to Oligo-Miocene siliciclastic, carbonate and evaporitic sequences, a complex of tectonic slices that include portions of the Tuscan Nappe and the underlying Hercynian metamorphic basement complex.…”
Section: Mediterranean Region Geothermal Systems: Larderellomentioning
confidence: 98%
“…The mid-crustal low velocity anomaly (-30%) is about double the amplitude of most teleseismic tomography results from other volcanic centers around the world (Iyer, 1988;Iyer and Dawson, 1993). Some exceptions are the teleseismic tomography study of Foley et al (1992), which imaged a structure beneath the Larderello geothermal field in Italy with a comparable anomaly, and the teleseismic P wave polarization study of Steck and Prothero (1994), which found a velocity anomaly of about-30% at Long Valley. The high amplitude may be due simply to relatively greater proportions of partial melt being present in the crust beneath the Valles caldera because of recent reheating , 1994).…”
Section: The Main Model Features Obtained In Inversions Using Both Tmentioning
confidence: 99%